2017
DOI: 10.1016/j.physbeh.2017.05.014
|View full text |Cite
|
Sign up to set email alerts
|

Sleep quality and duration are associated with performance in maximal incremental test

Abstract: Sleep duration and quality are associated, at least in part, with performance during maximal incremental test among healthy men, with losses in W and HR. In addition, our results suggest that the relationship between sleep patterns and performance, mainly in W, is independent of fitness condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
12
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 25 publications
5
12
0
2
Order By: Relevance
“…A decrease in maximal oxygen uptake measured in an incremental maximal exercise test due to a shorter duration of sleep as well as lower quality of sleep was previously reported. 44 The researchers reported oxygen uptakes of 44-59mL•Kg -1 •min -1 , which are comparable with the results of this study. 44 The result of this study show that for the most part, subjects were able to achieve slightly higher HRmax values, which could be explained by the fact that they were somewhat younger in age.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…A decrease in maximal oxygen uptake measured in an incremental maximal exercise test due to a shorter duration of sleep as well as lower quality of sleep was previously reported. 44 The researchers reported oxygen uptakes of 44-59mL•Kg -1 •min -1 , which are comparable with the results of this study. 44 The result of this study show that for the most part, subjects were able to achieve slightly higher HRmax values, which could be explained by the fact that they were somewhat younger in age.…”
Section: Discussionsupporting
confidence: 90%
“…44 The researchers reported oxygen uptakes of 44-59mL•Kg -1 •min -1 , which are comparable with the results of this study. 44 The result of this study show that for the most part, subjects were able to achieve slightly higher HRmax values, which could be explained by the fact that they were somewhat younger in age. 44 In a study from 2017, recovery was influenced for the worse by one night of partial sleep deprivation.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In our study, users were considered to have normal sleep values if their weekly sleep average was less than 0•5 SD below their overall sleep average, as nights of short sleep duration have been shown to result in elevated heart rate the following day. 19,20 We found that our correlations improved slightly when we classified people as displaying normal values when they had low sleep. In the future, improved measurements of stress by wearable devices, either by detection of voice changes or galvanic skin response, could further improve our ability to identify other non-infectious causes of elevated RHR.…”
Section: Discussionmentioning
confidence: 79%
“…However, these sports and exercise related adverse effects do not result from the sports itself, but from the difficulties in biological clock adjustment due to the aforementioned economic pressure in such branches of sports 21 . It was demonstrated that sleep helped gaining full power after an intensive training session, which was also coined as "You can gain the full power of the sleep-sweat" 22 . Since research on sleep-exercise relationship is generally applied on small populations, power of current evidence with respect to the positive effect of exercise on sleep is being discussed and speculated on a certain extent.…”
Section: Sedentary N=30mentioning
confidence: 99%